Energetic analysis on AP-X process for liquefaction of natural gas using open source software - Mohd Khairulnazreen Zahari (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main objective of this thesis is to model a single mixed refrigerant process for offshore natual gas liquefaction using DWSIM as a similation tool. Liquefied natural Gas (LNG) in the energy sector is seen as a realistic source for providing cleaner, small to large scalr fuel, due to the ever-inceasing global environmental protection and high demind of electricity at a competitive rate.